2014
DOI: 10.1111/oik.02004
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary irony: evidence that ‘defensive’ plant spines act as a proximate cue to attract a mammalian herbivore

Abstract: Many plants produce structural defenses to deter feeding by herbivores. However, many previous studies testing whether spines are eff ective at defending against mammalian herbivores have produced equivocal results. Th ese ambiguous results are hypothesized to be due to herbivore counter-adaptations. We investigated potential counter-adaptations in a population of white-throated woodrats Neotoma albigua that specialize on cactus by investigating feeding behavior and preference for cacti varying in spinescence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…cactus pads, the main component of the natural diet for this population [18]. Following the methods of Kohl et al [18], we further analyzed stable isotopes from hair of collected woodrats and confirmed that these individuals specialized on cacti ( Fig. S1).…”
Section: Animal Collectionsupporting
confidence: 54%
See 1 more Smart Citation
“…cactus pads, the main component of the natural diet for this population [18]. Following the methods of Kohl et al [18], we further analyzed stable isotopes from hair of collected woodrats and confirmed that these individuals specialized on cacti ( Fig. S1).…”
Section: Animal Collectionsupporting
confidence: 54%
“…The white-throated woodrat (Neotoma albigula) is an excellent model system to explore gut microbial changes associated with lifestyle modifications imposed by captivity, because their natural diet can be replicated in captive settings. Although N. albigula is considered a generalist herbivore, certain populations in the southwest of the United States feed almost exclusively on cacti of the genus Opuntia [18,19]. We took advantage of this dietary specialization and the feasibility of recreating the natural diet in captive conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of secondary metabolites, analyzed by phytochemical profiling, has allowed the identification of the principal compounds in the stem (Loza-Cornejo et al, 2017), the structural chemical composition of stem conductive tissues (Reyes-Rivera et al, 2015; Maceda et al, 2018; Reyes-Rivera et al, 2018), and from other structures such as glochids and spines in several cacti species (Pritchard and Hall, 1976; Kohl et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many plants employ structural defenses such as spines, hairs, or thickened leaves (reviewed by Hanley et al 2007;Farmer 2014), and some herbivores have developed counter-adaptations to spinescent plants. The caterpillar Hyphantria cunea consumes the central portion of spinescent holly leaves (Potter and Kimmerer 1988), while the woodrat Neotoma albigula removes the spines when feeding on spinescent cactus leaves (Kohl et al 2015). The oak Q. acutissima in this study also has several spines along each leaf margin (see Fig.…”
Section: Discussionmentioning
confidence: 70%